Comparative analysis of the relative potential of silver, Zinc-oxide and titanium-dioxide nanoparticles against UVB-induced DNA damage for the prevention of skin carcinogenesis. Issue 1 (1st December 2016) - Tyagi, Nikhil; Srivastava, Sanjeev K.; Arora, Sumit; Omar, Yousef; Ijaz, Zohaib Mohammad; AL-Ghadhban, Ahmed; Deshmukh, Sachin K.; Carter, James E.; Singh, Ajay P.; Singh, Seema
Abstract: Sunscreen formulations containing UVB filters, such as Zinc-oxide (ZnO) and titanium-dioxide (TiO2 ) nanoparticles (NPs) have been developed to limit the exposure of human skin to UV-radiations. Unfortunately, these UVB protective agents have failed in controlling the skin cancer incidence. We recently demonstrated that silver nanoparticles (Ag-NPs) could serve as novel protective agents against UVB-radiations. Here our goal was to perform comparative analysis of direct and indirect UVB-protection efficacy of ZnO-, TiO2 - and Ag-NPs. Sun-protection-factor calculated based on their UVB-reflective/absorption abilities was the highest for TiO2 -NPs followed by Ag- and ZnO-NPs. This was further confirmed by studying indirect protection of UVB radiation-induced death of HaCaT cells. However, only Ag-NPs were active in protecting HaCaT cells against direct UVB-induced DNA-damage by repairing bulky-DNA lesions through nucleotide-excision-repair mechanism. Moreover, Ag-NPs were also effective in protecting HaCaT cells from UVB-induced oxidative DNA damage by enhancing SOD/CAT/GPx activity. In contrast, ZnO- and TiO2 -NPs not only failed in providing any direct protection from DNA-damage, but rather enhanced oxidative DNA-damage by increasing ROS production. Together, these findings raise concerns about safety of ZnO- and TiO2 -NPs and establish superior protective efficacy of Ag-NPs. Highlights: Ag-, ZnO- and TiO2 -NPs provide significant photoprotection against UVB in HaCaT cells. AgNPs provide biological protection against UVB-DNA damage through NER mechanism. ZnO- and TiO2 -NPs promote, while AgNPs suppresses reactive oxygen species generation. AgNPs enhance SOD/CAT/GPx activity to counterbalance UVB-induced oxidative stress.